2018
DOI: 10.1007/s00198-018-4558-x
|View full text |Cite
|
Sign up to set email alerts
|

Quality indicators for hip fracture care, a systematic review

Abstract: Quality indicators are used to measure quality of care and enable benchmarking. An overview of all existing hip fracture quality indicators is lacking. The primary aim was to identify quality indicators for hip fracture care reported in literature, hip fracture audits, and guidelines. The secondary aim was to compose a set of methodologically sound quality indicators for the evaluation of hip fracture care in clinical practice. A literature search according to the PRISMA guidelines and an internet search were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
55
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 54 publications
0
55
0
1
Order By: Relevance
“…One‐year mortality was not assessed. Several other studies, however, did not report reduction of mortality with early surgery …”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…One‐year mortality was not assessed. Several other studies, however, did not report reduction of mortality with early surgery …”
Section: Discussionmentioning
confidence: 95%
“…Multiple quality indicators of hip fracture care, such as structure, process, and outcome, were proposed in recent years. One systematic review identified 97 unique quality indicators, not all of which correlated with outcomes . The time‐to‐surgery indicator was defined by different studies as being 24, 36, or 48 hours.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The level of pre-fracture mobility has proven to be an important predictor for 30-day mortality in frail hip fracture patients [ 12 , 13 ]. In addition, a mobility score can be used to monitor the post-operative recovery process, and the return to pre-fracture mobility is used as a quality indicator [14] . The mobility score that the Fragility Fracture Network (FFN) decided to use for audits on care for hip fracture patients, is the Fracture Mobility Score [15] .…”
Section: Introductionmentioning
confidence: 99%